Teachers' viewpoint on online courses - Päivi Kinnunen; Taina Eriksson (Portugal, 2022)
Many universities that have previously focused on offering blended learning or face to face courses are currently starting to offer more and more also online courses. This paper takes a closer look at the background and perceptions of eight teachers who are about to teach an online course for the first time. More specifically, we take a look at the teachers' perceptions of themselves as adopters of new pedagogy and new technology as well as their perceptions of strengths and weaknesses of online courses. The preliminary results suggest that our teachers feel rather comfortable with the new technology and especially with the new teaching methods. Most of the teachers identified themselves as innovators or early adopters of new teaching methods. Teachers perceived flexibility and efficiency as the most prevailing strengths of online teaching. On the other hand, weaknesses included workload, technical challenges, and various topics that relate to the lack of face to face interaction. We conclude by discussing what kind of pedagogical support and training the online teachers would benefit from.
Proceedings of the 10th International Conference on Computer Supported Education - Volume 1: CSEDU